Infectivity of HBV and screening strategy. (28th July 2014) - Tadokoro, K.; Satake, M.
Abstract : Hepatitis B virus (HBV) remains the most frequent cause of transfusion‐transmitted viral infection. HBV is highly infectious with minimal 50% chimpanzee infectious dose (CID50 ) of 10 copies at the pre‐acute phase of infection. However, HBV is not always infectious via transfusion. The infectivity of HBV depends on (1) viral properties such as viral load, phase of infection, genotype and genome mutations, (2) transfusion factors such as blood volume, types of components, concurrent transfusion of anti‐HBs‐positive blood, and (3) recipient factors such as extant anti‐HBs acquired either by natural infection or vaccination, immune‐competence. The risk of HBV infections remaining after HBsAg screening is associated with donations during the preseroconversion window period and of occult HBV infection. Each country needs to establish its own HBV screening strategy considering the prevalence of HBV, the residual risk of HBV transmission, the balance between blood safety and securing sufficient amounts of blood, cost‐effectiveness, and public perception of the risk of transfusion‐transmitted HBV.